1999
DOI: 10.1073/pnas.96.7.4125
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic factors [activity-dependent neurotrophic factor (ADNF) and basic fibroblast growth factor (bFGF)] interrupt excitotoxic neurodegenerative cascades promoted by a PS1 mutation

Abstract: Although an excitotoxic mechanism of neuronal injury has been proposed to play a role in chronic neurodegenerative disorders such as Alzheimer's disease, and neurotrophic factors have been put forward as potential therapeutic agents, direct evidence is lacking. Taking advantage of the fact that mutations in the presenilin-1 (PS1) gene are causally linked to many cases of early-onset inherited Alzheimer's disease, we generated PS1 mutant knock-in mice and directly tested the excitotoxic and neurotrophic hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 66 publications
(91 reference statements)
2
62
0
1
Order By: Relevance
“…Consistently, FGF-2 has been found to afford protection toward the endothelial damage produced by gp120, an HIV-derived cytoxic protein, 26 as well as to shield neuronal cells from the excitotoxicity induced by Ab peptides. 27 Conceivably, a mechanism that explains the Ab 1-40 toxicity, is the observed disruption of the FGF-2 binding to heparin, a membrane molecule that regulates its subsequent binding to the high-affinity receptor. 19 The marked reduction of FGFR1 phosphorylation following exposure to Ab 1-40 , constitutes prima facie evidence that the above mechanism may be operant and may trigger the toxic injuries, as it deprives the endothelium of the tonic FGF-2 input necessary for its survival.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, FGF-2 has been found to afford protection toward the endothelial damage produced by gp120, an HIV-derived cytoxic protein, 26 as well as to shield neuronal cells from the excitotoxicity induced by Ab peptides. 27 Conceivably, a mechanism that explains the Ab 1-40 toxicity, is the observed disruption of the FGF-2 binding to heparin, a membrane molecule that regulates its subsequent binding to the high-affinity receptor. 19 The marked reduction of FGFR1 phosphorylation following exposure to Ab 1-40 , constitutes prima facie evidence that the above mechanism may be operant and may trigger the toxic injuries, as it deprives the endothelium of the tonic FGF-2 input necessary for its survival.…”
Section: Discussionmentioning
confidence: 99%
“…Also, N141I-PS2 augments death in PC12 cells (Wolozin et al, 1996). FAD mutant PS1 enhances death in PC12 cells (Guo et al, 1996;Weihl et al, 1999) and primary neurons (Czech et al, 1998;Zhang et al, 1998;Guo et al, 1999;Weihl et al, 1999). Rohn et al (2000) and Sudo et al (2000Sudo et al ( , 2001 independently found that treatment of neuronal cells with anti-APP antibody remarkably enhances the neurotoxic function of wild-type (wt) APP, whose overexpression could cause AD type of neurodegeneration in Down's syndrome.…”
mentioning
confidence: 99%
“…Previous studies have characterized these mice, showing that the knock-in mice express mutant PS1 at normal levels. PS1 mutant mice have no overt developmental abnormalities, but do exhibit increased levels of Ab 1-42 in brain tissue and increased vulnerability of hippocampal neurons to apoptosis and excitotoxicity (Guo et al 1999a(Guo et al , 1999b.…”
Section: Methodsmentioning
confidence: 99%
“…PS1 is an integral membrane protein expressed in neurons throughout the brain where it is localized primarily in the endoplasmic reticulum (ER). Two pathogenic mechanisms for PS1 mutations have been proposed, the first involving altered proteolytic processing of the amyloid precursor protein, resulting in increased production of neurotoxic forms of amyloid betapeptide Selkoe 2001), and the second involving perturbed ER Ca 2+ regulation resulting in excessive increase of intracellular Ca 2+ levels under conditions of oxidative and excitotoxic stress (Guo et al 1996(Guo et al , 1997(Guo et al , 1999a(Guo et al , 1999b). …”
mentioning
confidence: 99%